ANALISIS OPERASIONAL ANGKUTAN UMUM DI KABUPATEN BUTON - AKSA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Public Passenger Car (MPU) is a mode of land transportation with operating systems operating in various sizes. In the Buton Regency, the fleet is operated by medium-sized buses and small buses for rural transportation. In the operation of the MPU, service to service users is a top priority that must be considered and prioritizes safety that is carried out properly by the operator / owner of the MPU. This study aims to find out and analysis how much the level of expectation and performance of MPU entrepreneurs in Buton Regency on service perceptions, tariffs and routes and to find out and analysis how much the level of expectation and performance of Buton District Transportation Service Officers in MPU services in Buton Regency on service perception , Tariff and Route Analysis of the level of importance and performance in the five dimensions of service quality consisting of reliability, responsiveness, assurance, empathy, physical evidence (Tangible) and perception of tariffs and routes to measure expectations and MPU performance. The data analysis of this research was conducted using a descriptive qualitative method to answer the problem formulation of how the expectations of the operators / owners of MPUs and service users towards MPU operations on perceptions of service quality, tariffs and routes, then used "Importance Performance Analysis", with a total sample of 100 respondents. consisting of 50 MPU service user respondents in Buton District and 50 MPU operator / owner respondents in Buton Regency. The results of the expectation level and the performance of the operator and owner of the MPU in Buton Regency. From 5 for the sake of service the highest value was an average of 79.94% in empathy perceptions and the lowest was an average value of 71.68% in the perception of reliability. Route and Perception Rates From the results of the analysis address perceptions of routes and tariffs in Buton Regency, the total value is 79.90%. For the performance and expectations of Buton District Transportation Department officers in providing services to service users and operators / owners of the MPU on average a total of 74.36%